Investigation of the inverse piezoelectric effect of synchrotron light source imaging of electrical stimulation on the fate of nano stem cells and its role and application in regenerative medicine and cancer treatment - Heidari, Alireza; Torfeh , Zahra; Iorgulescu , Sophia; Robinson , Olivia; Hu, Lin; Vauclin , Charlotte; Schiltz , Ntalie; Sondermann , Scarlett; MacLennan, Lucy; Smith , Julia; Williamson , Lydia (International Journal of Advanced Chemistry, 2022)
The presence of electrical activity in body organs such as the nervous system, heart and bones has caused one of the most widely used treatment methods called electrotherapy to be widely used, especially in the relief of underlying pain. On the other hand, the progress of medical science in the field of nano stem cells and regenerative medicine has created many promises in treatment. Also, recently, treatments based on electric field have been widely used in cancer treatment. The main issues in regenerative medicine are the proliferation of nano stem cells to the required extent and directing them towards the differentiation of the target tissue. Electric field (EF) stimulation can play an important role in creating appropriate nano stem cell responses and directing nano stem cell differentiation towards osteogenesis/neuronogenesis/cardiomyogenesis. The electric field with nanosecond pulse as well as the electric field for tumor therapy have attracted a lot of attention for the treatment of cancer. Major signaling pathways and cellular responses elicited by electrical stimulation include reactive oxygen species and heat shock proteins, fluctuations in intracellular calcium ion concentration, ATP production, clustering or reaggregation of cell surface receptors., reconstruction of the cytoskeleton that affect the fate of the nano stem cell. Also, the lack of pain, ease and reasonable price have made cancer treatment with electric field more and more popular. In this research, an attempt has been made to briefly review the effects of electrical signals on the behavior of nano stem cells, as well as examples of their therapeutic effects in the treatment of tissue lesions and cancer.Schematic of the inverse piezoelectric effect of synchrotron light source imaging of electrical stimulation on the fate of nano stem cells and its role and application in regenerative medicine and cancer treatment.